To the Beat of Their Own Drum: Women in Salsa - Poey, Delia (Complutense Journal of English Studies, 2015)
Salsa music is a Pan-Latino form of cultural expression born of an American experience. While its roots are varied—primarily but not exclusively Cuban and Puerto Rican, it mixes tradition and innovation, privileging mixture. Although much has been written about Salsa in the last fifteen years, the contributions of women as performers have been large ignored. This paper attempts to fill in that gap by arguing that Salsa, as an American music, was enriched by early contributions of two female performers, Celia Cruz and La Lupe. By engaging with the music scene in New York, these women reinvented themselves as Salsa stars in the 1960s and early 70s. Their stage performances and personas, however, were markedly different— particularly their staging of race and gender. Cruz became “the lady,” while La Lupe’s performances were marked by frenzy and excess. Both also worked within established racial codes that would seek to constrain performative possibilities for black women. They simultaneously, although in different ways, played into and challenged those racial codes thereby contributing to this uniquely American sound.